Bimbingan Kelompok Dengan Teknik Sosiodrama Untuk Meningkatkan Pemahaman Tentang Etika Berbicara Siswa - Alfaria Christin, Rusviani; Karuniaty Sangalang, Oktamia; Br Ginting, Herda Fitri (Universitas Palangka Raya, 2024)
The purpose of this study was to improve the understanding of speaking ethics by giving Group Guidance using Sociodrama Technique. This research uses experimental quantitative method with the design of “one group pretest-postest design”, the sample in the research from class XI MIPA 4 SMA Negeri 2 Palangka Raya which amounted to 6 students as samples with purposive sampling technique. Based on the research results, it is known that the descriptive results before being given group guidance services with sociodrama techniques, the average percentage of understanding of speaking ethics is 34.16%. Descriptive results of understanding of speaking ethics are low, after being given group guidance services with sociodrama techniques, the average percentage of 42.83% is included in the high classification. It is known that t count -14.100> t table -4.032 using the paired sample t test. Then the Ho hypothesis is rejected and Ha is accepted. This shows that “group guidance services with sociodrama techniques can improve understanding of speaking ethics of students in class XI MIPA SMA Negeri 2 Palangka Raya”.